2020
DOI: 10.3389/fcell.2020.00121
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Glaucomatous Optic Neuropathy

Abstract: Autophagy is a conserved lysosomal-dependent pathway responsible for the degradation of cytoplasmic macromolecules. Based on the mechanism of cargo delivery to lysosomes, mammalian cells can undergo micro, macro, and chaperonemediated autophagy. Other than physiological turnover of proteins and organelles, autophagy regulates cellular adaptation to different metabolic states and stressful conditions by allowing cellular survival or, when overactivated, participating to cell death. Due to their structure and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Overall, an impairment of autophagy due to oxidative stress is related with several age-related eye diseases such as dry eye diseases, corneal dystrophy type 2, cataracts and retinal dystrophies like AMD, glaucoma, DR, and retinal artery occlusion [51,52].…”
Section: Autophagy and Oxidative Stressmentioning
confidence: 99%
“…Overall, an impairment of autophagy due to oxidative stress is related with several age-related eye diseases such as dry eye diseases, corneal dystrophy type 2, cataracts and retinal dystrophies like AMD, glaucoma, DR, and retinal artery occlusion [51,52].…”
Section: Autophagy and Oxidative Stressmentioning
confidence: 99%
“…Potentially, the balance between autophagy and microglia can be regulated by pharmacological inhibition of, e.g., 3-methyladenine. Finally, studies indicate that some humans are genetically impaired of basal autophagy, which can impact retinal homeostasis and potentially promote retinal neurodegeneration, hereunder glaucoma ( 162 164 ). Future studies are needed to investigate further the partnership between autophagy and microglia as well as to elucidate further the interaction between microglia as well as other glia subtypes and RGCs.…”
Section: Microglia and Their Impact On Retinal Ganglion Cell Survivalmentioning
confidence: 99%
“…RGCs project their 1.2 million axons, composing the optic nerve, to the brain, transmitting the visual signals gathered by the retina, ultimately leading to formed vision in the visual cortex (Maresca et al., 2013 ; Carelli et al., 2017 ). Loss of RGCs is a common feature of optic neuropathies (Adornetto et al., 2020 ). It has been reported that the combined use of melatonin and Zoloft can result in the melatonin/dopamine imbalance in retina, manifesting as a toxic optic neuropathy (Lehman & Johnson, 1999 ).…”
Section: Discussionmentioning
confidence: 99%